Gap arthroplasty in a pediatric patient - case report (Research, Society and Development, 2020)
Ankylosis of the temporomandibular joint (TMJ) that occurs after fracture of the mandibular condyle constitutes a treatment challenge for oral and maxillofacial surgeons. It is a condition in which there is immobility of the joint, characterized by the formation of a bone, fibrous tissue or fibro-bone mass fused to the base of the skull. The most common factors for the progression of this condition are: trauma, systemic diseases and infections. The literature shows several ways of treatment such as: gap arthroplasty, interpositional gap arthroplasty using the temporal muscle, TMJ reconstruction using costochondral graft and alloplastic reconstruction of the joint. In view of this, this article aims to report the case of a child victim of trauma (cycling accident), diagnosed with a high fracture in the left mandibular condyle and to demonstrate the possibility of evolution of the fracture in ankylosis of the TMJ and, in sequence, to show the effectiveness of the surgical treatment performed by gap arthroplasty associated with physiotherapy as a successful protocol in the treatment of TMJ ankylosis in a pediatric patient with 2 years of follow-up. The data were included through the search for journals, scientific articles and course completion papers found in the Pubmed, BVS and Capes databases.